Production of phenolic compounds using waste coir pith: Estimation of kinetic and thermodynamic parameters. (February 2019) - Awasthi, Ayushi; Dhyani, Vaibhav; Biswas, Bijoy; Kumar, Jitendra; Bhaskar, Thallada
Graphical abstract: Highlights: Coir pith waste is massively generated from coir fiber processing industries. It can be pyrolyzed to obtained bio-oil rich in phenolic compounds. Up to 88.14% phenolics were obtained in the organic fraction of bio-oil. A parallel kinetic analysis can help in process optimization. Abstract: The present study illustrates the production of phenolic compounds via slow pyrolysis of coir pith biomass in a bench-scale reactor. The primary objective of the study is to optimize the pyrolysis conditions to maximize the yield of bio-oil and phenolic compounds. Up to 88.14% phenolic compounds were obtained in the organic fraction of the bio-oil obtained at 350 °C. The phenolic compounds thus extracted can be used for the production of phenol-formaldehyde resins, which reduces the dependence on petroleum-based phenols for the manufacturing of resin. An independent kinetic analysis of the apparent pyrolysis reaction was also performed using thermogravimetry and isoconversional methodology. The calculated values of activation energy showed a variation from 28.41 to 200.09 kJ/mol, with the mean value being 140 kJ/mol. The thermodynamic parameters (ΔS, ΔH, and ΔG) were subsequently evaluated at different conversions using the activation energy values obtained from the kinetic analysis.